Evaluasi Cemaran Aflatoksin B1 pada Pakan Ayam Pedaging Komersial Di Kota Kupang - Devi Y. J. A. Moenek (JURNAL KAJIAN VETERINER, 2019)
Aflatoxin B1 is a secondary metabolite of Aspergillus flavus, Aspergillus parasiticus, and Penicillium puberulum, which is frequently found as contaminants of feed/raw materials of poultry feed. Such compound has the toxic and carcinogenic effects that can cause damage to various organs, which can further decrease the performance of broiler, and various degrees of immunosuppressive effects.This study was designed to evaluate the aflatoxin B1 contamination on commercial broiler feed that is given to 10 broiler farms in Kupang City. Physical examinations followed by a qualitative examination using ultraviolet (UV). Analysis of aflatoxin B1 contamination was performed with high performance liquid chromatography (HPLC). The results of physical examination of feed will be analyzed descriptively, whereas the contamination levels of aflatoxin B1 will be analyzed statistically using t-test. Based on the results, it can be concluded that the texture of feed in the storage of farms was not changed, whereas the left over feed indicated an irregular texture, which was crushed, moist, lumpy, sour-smelling, and glowing on irradiation with UV light. Statistical analysis using t-test showed no significant difference (P>0.05) in the level of aflatoxin B1 among of feed samples from the storage and left over feed.